Vitamin C and Helicobacter pylori Infection: Current Knowledge and Future Prospects - Mei, Haixin; Tu, Hongbin (Frontiers in Physiology, 2018)
The gram-negative bacterium, Helicobacter pylori (H. pylori), infection is predominantly known for its strong association with development of gastric diseases, including gastritis, peptic ulcers, and stomach cancer. Numerous clinical reports show that ascorbic acid deficiency has been connect with gastritis. Vitamin C levels both in gastric acid and serum have constantly been affirmed to be low in subjects with H. pylori infected gastritis and peptic ulcers. Ascorbic acid supplementation likely relates to reduced incidences of bleeding from peptic ulcers and gastric cancer. H. pylori eradication is shown to increase vitamin C levels, while the benefits of ascorbic acid oral intake to increase the effectiveness of H. pylori-eradication therapy are controversial. Recent studies suggest that ascorbate intake intravenously, but not orally; pharmacologic ascorbate concentrations up to 30 mmol/L in blood, several millimolar in tissues as well as in interstitial fluid, are easily and safely achieved. Pharmacologic ascorbate can exert pro-oxidant effects locally as a drug by mediating hydrogen peroxide (H2O2) formation, which was applied to animal and clinical trials of cancer, sepsis, and severe burns etc. In this review, we summarize current understanding of the associations of vitamin C and H. pylori infection, and outline some potential strategies for H. pylori intervention from emerging advances on ascorbic acid physiology and pharmacology.